Asymmetric Janus functionalization induced magnetization and switchable out-of-plane polarization in 2D MXene Mo2CXX′. Issue 12 (9th March 2023) - Xin, Chao; Fan, Zhen; Sun, Zhixin; Li, Hui; Jin, Guangyong; Pan, Feng; Sui, Yu
Abstract : A fair high T C of 303 K is predicted for Mo2 C-FO. Our DFT+ U calculation results also provide a mechanism of magnetoelectric coupling, in which the reversal of electric polarization is driven by terminal-layer atom-pair flipping. Abstract : Exploring two-dimensional (2D) van der Waals materials with out-of-plane polarization and electromagnetic coupling is essential for the development of next-generation nano-memory devices. A novel class of 2D monolayer materials with predicted spin-polarized semi-conductivity, partially compensated antiferromagnetic (AFM) order, fairly high Curie temperature, and out-of-plane polarization is analyzed in this work for the first time. Based on density functional theory calculations, we systematically studied these properties in asymmetrically functionalized MXenes (Janus Mo2 C)-Mo2 CXX′ (X, X′ = F, O, and OH). Using ab initio molecular dynamics (AIMD) and phonon spectrum calculations, the thermal and dynamic stabilities of six functionalized Mo2 CXX′ were identified. Our DFT+ U calculation results also provided a switching path for out-of-plane polarizations, where the reverse of electric polarization is driven by terminal-layer atom flipping. More importantly, strong coupling between magnetization and electric polarization originating from spin-charge interactions was observed in this system. Our results confirm that Mo2 C-FO would be a novel monolayer electromagnetic material, and its magnetization can be modulated by electric polarization.